STUDY OF THE EFFECTIVENESS OF THE DRUG BELMAK 5% EM.K AGAINST MELON FLY (CARPOMYA PARDALINA BIGOT) IN THE CONDITIONS OF THE KHOREZM REGION - Sadullayev Sanjarbek Madiyarovich; Komilova Sohiba Qadamboy qizi (Bright Mind Publishing, 2025)
In this article, the degree of harm caused by the melon fly pest to melons is studied, and it is aimed to increase the effectiveness of agrotechnical measures to achieve high efficiency in the fight against it by using chemical preparations and to save the cultivated crop.
Keywords: Melon fly, mother, larva, phase, meat part, enzyme, drug.